Geopolitics of the Knowledge-Based Economy (Edition 1) - Moisio, Sami (Taylor & Francis, 2018)
We live in the era of the knowledge-based economy, and this has major implications for the ways in which states, cities and even supranational political units are spatially planned, governed and developed. In this book, Sami Moisio delves deeply into the links between the knowledge-based economy and geopolitics, examining a wide range of themes, including city geopolitics and the university as a geopolitical site. Overall, this work shows that knowledge-based "economization" can be understood as a geopolitical process that produces territories of wealth, security, power and belonging. This book will prove enlightening to students, researchers and policymakers in the fields of human geography, urban studies, spatial planning, political science and international relations.